Studentsâ€™ Metacognitive Skills from the Viewpoint of Answering Biological Questions: Is It Already Good? (Jurnal Pendidikan IPA Indonesia, 2019)
Recent research in the science learning field emphasizes the importance of science learning that can empower 21st Century skills and implement metacognition-based learning. Metacognition is one of the foremost successful factors of learning achievement, which is the implementation in Indonesian schools is still being questioned. The present quantitative study aimed at gathering information on the profile of studentsâ€™ metacognitive skills in Malang and figuring out whether the studentsâ€™ grader influence metacognitive skills or not. This study was in ex post facto research which involves five levels of independent variables (grade level) and metacognitive skills as the dependent variable. The study involved 458 students (99 students in grade VII, 98 students in grade VIII, 98 students in grade IX, 77 students in grade X, and 86 students in grade XI) as the participants selected by homogeneous purposive sampling technique. The data of the metacognitive skills were collected by using Metacognitive Skills Rubric integrated with essay questions as the instrument. The collected data were analyzed through descriptive statistics and one-way ANOVA. The results of this study informed that the studentsâ€™ metacognitive skills in Malang at each grade were categorized in â€œvery lowâ€. However, the level of grade significantly influenced the studentsâ€™ metacognitive skills. The Senior High School (SHS) students possessed the highest level of metacognitive skills, and the students of grade VII of Junior High School (JHS) were at the lowest level. Senior High School students have better metacognitive skills than JHS students due to this kind of skills could develop by the increase of studentsâ€™ grades in the process of education. The findings of this study also reveal the low level of studentsâ€™ metacognitive skills. Therefore, the learning process is recommended to implement various learning form that can empower studentsâ€™ metacognitive skills optimally.